EFEKTIVITAS PROGRAM NASIONAL PEMBERDAYAAN MASYARAKAT MANDIRI PERKOTAAN (PNPM–MP) DI KOTA PALU - Machfiroh, Asfriqi (Katalogis, 2015)
Objective this research is to measure the effectiveness of National Program implementation for independent Urban Community Empowerment in Palu. Informants in this research are those directly involved with the National Program for independent Urban Community Empowerment in Palu. This research is a qualitative research. The methods used in collecting data are: in-depth interviews, direct observation, and Documentation.Based on the research results, the implementation of National Program for independent Urban Community Empowerment in Palu has been effective, in terms of process it is going according to the cycle stages of implementation of National Program for independent Urban Community Empowerment in Palu. The implementation is conducted through several stages, namely: Socialization, planning, implementation and evaluation stage. This process is already carried out quite well, judging from the number of activities that have been accomplished. There are several factors that affect the successful of implementation of National Program for independent Urban Community Empowerment in Palu namely public support, good communication between the consultant and Community Self-Reliance Agency at village level, and the executive attitude is manifested by having executive commitment in terms of togetherness to build social environment. The fundamental matter that needs to be improved is to develop the participation attitude of citizen to be involved more actively in the implementation of of National Program for independent Urban Community Empowerment.